Customer-driven supply chains under IMP lens: A systematic literature review and conceptual framework. Issue 2 (12th June 2017) - Martinelli, Elisa Martina; Tunisini, Annalisa; Guercini, Simone
Abstract : Purpose: This paper explores the most recent contributions to interpreting customer-driven supply chains (CDSCs) under the IMP lens, focusing on the main characteristics that emerged from a review of the relevant literature. The purpose of this paper is to offer a holistic interpretative framework of major topics covered by the CDSC literature, highlighting both some shared issues and emerging elements using the IMP conceptual framework's ARA (actor bonds, activity links and resource ties) model. Design/methodology/approach: The paper reviewed the literature by searching selected journals using a combination of specific keywords in order to find the most recent contributions on the CDSC theme. The presented analysis allowed an interpretation of the findings through a conceptual framework. Findings: The findings suggest that the ARA model could be a useful method through which to structure an interpretation of the most recent contributions, in both IMP and the general literature, on the discipline. In particular, three streams of research were identified: the customer closeness strategy, relational strategy, and intra-organizational strategy. Research limitations/implications: These clusters can be deeply analyzed using the major knowledge on CDSC dynamics. By studying these issues in an integrated way, the implications in terms of competition, generalization of results, constraints, problems, and difficulties of the customer-driven approach could be enhanced. Limitations are the restricted period of time and the absence of empirical research. Practical implications: Each identified cluster presents the tools that have to be improved in order to implement the customer-driven orientation, which increases the performance and brings an added value for the same supply chain. For this reason, an emerging need is to develop studies on the empirical side that consider the implications in terms of an integrated framework among the three issues. Originality/value: The paper increases the understanding of CDSCs by using conceptual and interpretative tools developed by the IMP literature. The ARA model allows the creation of a conceptual framework that clarifies, in a holistic way, the most important characteristics that have to be developed in order to improve the CDSC perspective. Recommendations and a research agenda for the implementation of the customer-driven view are derived.